2023
DOI: 10.1039/d2ta08213f
|View full text |Cite
|
Sign up to set email alerts
|

A charge-free and membrane-free hybrid capacitive mixing system for salinity gradient energy harvesting

Abstract: Capacitive mixing (CapMix) is a promising technology to harvest the salinity gradient energy (SGE) by generating electricity through the potential difference owing to electrolyte salinity change at the electrode/electrolyte interface....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The power density values of existing EDL-based membrane-free systems are below 65 mW/m 2 [ 29 , 32 , 42 ]. Other technologies, such as battery mixing and hybrid mixing, have been reported to achieve a maximum power density of about 98 mW/m 2 under a 0.6 M to 0.01 M salinity gradient for membrane-free and charge-free operations [ 58 , 59 ] (Table S5 ). In contrast, our research has demonstrated that proper surface modifications can increase the power density to 166 mW/m 2 for a 0.6 M to 0.01 M gradient.…”
Section: Discussionmentioning
confidence: 99%
“…The power density values of existing EDL-based membrane-free systems are below 65 mW/m 2 [ 29 , 32 , 42 ]. Other technologies, such as battery mixing and hybrid mixing, have been reported to achieve a maximum power density of about 98 mW/m 2 under a 0.6 M to 0.01 M salinity gradient for membrane-free and charge-free operations [ 58 , 59 ] (Table S5 ). In contrast, our research has demonstrated that proper surface modifications can increase the power density to 166 mW/m 2 for a 0.6 M to 0.01 M gradient.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Capacitive mixing (CapMix) represents one of the popular technologies to harvest blue energy. 9 The CapMix method is based on capacitive double-layer expansion (CDLE), which involves two electrodes submerged alternatively in the stream of seawater (SW) or freshwater (FW), forming a capacitor. By elaborately mixing SW and FW within the double layers continuously, we can collect the salinity gradient energy.…”
Section: Introductionmentioning
confidence: 99%
“…Once the electrode is saturated (or approaching saturation), the absorbed ions in the EDL are desorbed and released back into the process stream. 20,21 This step is known as the discharge process. An alternative platform to CDI is membrane capacitive deionization (MCDI).…”
Section: Introductionmentioning
confidence: 99%